A Cross-Sectional Survey Dataset on Infrastructure Resilience and Community Satisfaction in Coastal Reclamation Regions of Kota Kinabalu - Wilson Rangga, Anthony Jiram; Irwan, Sanjaya; Amanda Sophie, Junim; Azizah, Ismail; Fitriyah, Razali (CERN (European Organization for Nuclear Research), 2025)
This dataset presents cross-sectional survey data collected for a study on infrastructure resilience and community satisfaction in the coastal reclamation regions of Kota Kinabalu, Malaysia. The data were obtained from 237 respondents using a structured questionnaire designed to assess residents’ perceptions of resilient infrastructure and satisfaction with the built environment. Key constructs captured in the dataset include infrastructure networks, the ecological environment and land use, transportation systems, urban disaster reduction and building resilience, energy provision, and overall community satisfaction. Data analysis was performed using SPSS Version 26 for descriptive statistics and Partial Least Squares Structural Equation Modeling. The dataset confirms the reliability and validity of the proposed measurement model and supports empirical analysis of the relationship between infrastructure resilience and community satisfaction. It provides valuable empirical evidence to inform sustainable infrastructure planning and policy development in reclaimed urban coastal environments.